Osteoporosis is associated with elevated baseline cerebrospinal fluid biomarkers and accelerated brain structural atrophy among older people - Pan, Hao; Cao, Jiali; Wu, Congcong; Huang, Furong; Wu, Peng; Lang, Junzhe; Liu, Yangbo (Frontiers in Aging Neuroscience, 2022)
Objective: Examine whether osteoporosis (OP) is associated with Alzheimer's disease-related cerebrospinal fluid (CSF) biomarkers and brain structures among older people. Methods: From the Alzheimer's Disease Neuroimaging Initiative database, we grouped participants according to the OP status (OP+ / OP−) and compared the AD-related CSF biomarker levels and the regional brain structural volumes between the two groups using multivariable models. These models were adjusted for covariates including age, education, gender, diagnosis of Alzheimer's disease, and apolipoprotein E4 carrier status. Results: In the cross-sectional analyses at baseline, OP was related to higher CSF t-tau (total tau) and p-tau181 (tau phosphorylated at threonine-181) but not to CSF amyloid-beta (1-42) or the volumes of entorhinal cortex and hippocampus. In the longitudinal analyses, OP was not associated with the change in the three CSF biomarkers over time but was linked to a faster decline in the size of the entorhinal cortex and hippocampus. Conclusion: OP was associated with elevated levels of CSF t-tau and p-tau181 at baseline, as well as accelerated entorhinal cortex and hippocampal atrophies over time among older people.